Factors Affecting Decisions to Purchase Insurance for State Civil Services in Indonesia - Hisnil Fazri; Didik Wahyu Setiyadi; Aldi Mulyana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine the factors that influence the decision to purchase insurance for government employees. The factors tested consisted of Agent Competence, Service Quality and Company Credibility. Questionnaires were distributed to 250 people using the convenience sampling method through online questionnaires. Of the 250 questionnaires distributed, there are 210 questionnaires that have been completely filled out. Data testing is done with SPSS software. The results of this study found that company credibility has a significant effect on insurance purchasing decisions for Government employees (ASN), Service Quality has a significant influence on insurance purchasing decisions for ASN in Indonesia and the competence of insurance agents has no significant effect on insurance purchasing decisions for ASN in Indonesia. Indonesia. The Novelty / Value of this research lies in the object under study, namely government employees (ASN) who have never existed in previous research.